#TITLE_ALTERNATIVE# - IRAWAN (NIM 12203007), FIKRI
Steamflood is one of Enhanced Oil Recovery method by injecting continuous steam into reservoir with certain rate and steam quality. The obcjective is to increase oil mobility by reducing its viscosity to be produced through producer well. Before detail reservoir simulation, it is better to predict the reservoir performance by simple analytical method. This study compare three simple methods in predicting reservoir performance by using historical data from Field X. Gomaa generate several generalized curve which can be used by limitation of injection profile and reservoir characteristic. Myhill-Stegemeier assume that steam displacement to oil zone happens as frontal displacement after modifying Mandl and Volek correlation. And Neuman assume that injecting steam into reservoir will cause an existence of steam gravity override on top of the formation. The main objective of this study is to determine the best method which can approximate field production result based on calculation and analysis.